ANALISA PENGARUH FLEKSIBILITAS PASAR TENAGA KERJA ASIA TENGGARA TERHADAP PERFORMA PENJUALAN PT XYZ - Hanan, Winda Hafidhah; Arif, Moh. Erfan (Jurnal Kewirausahaan dan Inovasi, 2022)
The objective of this qualitative descriptive research is to analyze the effect of Southeast Asia’s labor market flexibility on the sales Performance of PT. XYZ, a company operating in Hong Kong, Singapore, Taiwan, Vietnam, Malaysia, and Indonesia. The labor market flexibility was measured using two types of flexibility according to Beatson (1995); they are quantity and price flexibilities. The data was harvested through semi-structured interviews with the samples, who were selected using key informant method, and analyzed using Miles & Huberman’s technique. This study finds that quantity flexibility can increase the number of jobs that can be covered by the recruitment services provided by PT. XYZ and increase the company’s sales performance. Furthermore, price flexibility can also increase the company’s sales performance because the labor-supplying countries have supplied lower-wage yet high-quality labors.